ISOLASI DAN UJI ANTIFUNGAL EKSTRAK METANOL, ETIL ASETAT DAN N-HEKSANA BAKTERI ENDOFIT DARI AKAR TUMBUHAN MENTIGI (Vaccinium varingaefolium) - Widya Lestari; Dwi Suryanto; Erman Munir (Universitas Negeri Medan, 2017)
Many study that endophytic bacteria useful for plant by protection mechanism to parasitic disease and recovery plant morphology using metabolite producing. Many plants such as mentigi grow at extreme area in volcanic mount. This plant can be able to has specific metabolite producing endophytic bacteria. Research about plant endophytic at extreme area are still limited. The aim of this research to know plant endophytic frommentigi root in inhibiting pathogen fungi growing. plantendophytic bacteria isolation from mentigi root was done by root surface sterilization, cutting and cultivating on nutrient agar medium. Cell extraction was done using methanol, etil-asetat and n-heksana for two isolates. Antagonis test isolates and cell extract was done to some plant and fish pathogen fungus such as Fusarium oxysporum, Ganoderma boninense, Rigidoporus microporusand Saprolegniasp. on potatoes dextrose agar contain 1% yeast extract. Isolates AW5 and AW6 have high potential in inhibiting plant pathogen fungi growing.Essay result extraction to plant pathogen fungi showed that methanol extract of isolate AW5 and AW6 have biggest potential in inhibiting pathogen fungi growing.